Terrorismo no Brasil? - Daniel Dory; Carlos Caserio (Confins)
The article analyses the data on Brazil in the Global Terrorism Database (GTD) and visualises it with commented maps. This database allows comparisons with other countries in the world, but obviously cannot claim to account for the diversity of local situations, but it does allow us to show that they are based on several logics and to construct a typology that reflects them. This leads us to explore related phenomena, such as the number of homicides, of which terrorism is only one of the causes